Investigation on the properties of epoxy asphalt mixture containing crumb rubber for bridge expansion joint. (9th May 2022) - Min, Zhaohui; Wang, Qichang; Zhang, Ke; Shen, Lei; Lin, Guofeng; Huang, Wei
Highlights: Epoxy asphalt binder for bridge expansion joint was proposed. Compared with BJ200, epoxy asphalt expansion joint shows superior high-temperature stability and moisture resistance. Rubber powder can improve the toughness of epoxy asphalt expansion joint at low temperature. Epoxy asphalt containing 30% CR can be recommended for bridge expansion joints. Abstract: The purpose of this research is to propose epoxy asphalt materials for bridge expansion joints. Epoxy asphalt was modified by adding 0%, 20%, 30% and, 40% crumb rubber (CR). The viscosity, tensile properties, adhesion, high-temperature stability, moisture resistance, low-temperature, and stress relaxation properties of rubber-modified epoxy asphalt (REA) were investigated comparing with the commercial BJ200-red. Thermal stress of epoxy asphalt expansion joint was also simulated by the finite element analysis platform. The results indicated that with the increase of CR content, the viscosity and deformation of REA binder increase, while operation time, the tensile strength, and adhesive decreases. CR has a slight negative effect on the high-temperature performance of epoxy asphalt mixture, and has a positive effect on low temperature deformation. When the rubber powder content is 30%, epoxy asphalt mixture has excellent mechanical properties and its high-temperature stability is higher than BJ200 mixture, but the low-temperature performance of the two is equivalent. Thermal stress analysis shows that epoxy asphalt containing 30% CR cannot fracture above −15 ℃, so it can be recommended for bridge expansion joints.